2014
DOI: 10.5430/jst.v4n3p4
|View full text |Cite
|
Sign up to set email alerts
|

P53 mutation compared with Ki67 marker in metastasis of breast cancer in western Iran

Abstract: Objective: To investigate and compare the prognostic value of P53 and Ki67 markers with age and metastasis and survival in patients with breast cancer in Kermanshah, western Iran. Methods: In our study on 116 patients with breast cancer that all of them were women and kind of pathology was invasive ductal carcinoma and patients had Her2 positive. The expression of ki67 marker and p53 genes were determined by immunohistochemistry. Statistical analysis was performed with SPSS version IBM 19 and Disease free surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Considering the fact that age had a significant relation with Ki67 in both groups, survival rate was assessed by removing the age from the equation to omit the age effect. However, some reports indicated that Ki67 did not have any prognostic value, and there was no relation between Ki67 and survival rate (Payandeh et al, 2014). In contrast, as mentioned before, in many other studies, the prognostic value of Ki67 has been frequently reported and this protein has been introduced as a predictive marker in recurrence (Kontzoglou et al, 2013;Inwald et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…Considering the fact that age had a significant relation with Ki67 in both groups, survival rate was assessed by removing the age from the equation to omit the age effect. However, some reports indicated that Ki67 did not have any prognostic value, and there was no relation between Ki67 and survival rate (Payandeh et al, 2014). In contrast, as mentioned before, in many other studies, the prognostic value of Ki67 has been frequently reported and this protein has been introduced as a predictive marker in recurrence (Kontzoglou et al, 2013;Inwald et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…The study in western Iran showed that the hazard ratios for P53 and Ki-67 were 1.37 and 0.52, respectively. Thus, P53 is more important than Ki-67 on survival rate [29]. Another study in eastern Iran demonstrated that Ki-67 had significant relationship with the survival rate, but over-expression of P53 did not show such a significance.…”
Section: Ki67 Scoringmentioning
confidence: 94%
“…Li et al studied 151 cases of breast cancer and found that Ki-67 did not relate to age, tumor size and lymph node status, whereas it correlated with tumor stage and P53 expression [28]. Two studies in Iran compared the prognostic value of P53 with Ki-67 in breast cancer and achieved contradictory results [29,30]. The study in western Iran showed that the hazard ratios for P53 and Ki-67 were 1.37 and 0.52, respectively.…”
Section: Ki67 Scoringmentioning
confidence: 99%